Geography of elections - Taylor, Peter John; Johnston, R. J. (Ronald John) (Routledge library editions. Political geography, 2015)
Within an international framework, this work provides a fully comprehensive approach to the geographical coverage of elections. Numerous applications of ideas and concepts from human geography are incorporated into a new political context, illustrating the manner in which electoral patterns reflect and help produce the overall geography of a region or state. Discussions of various topics are well supported by numerous maps and diagrams which help clarify arguments and serve to define elections within their basic geographical context.